Blood pH: a test for assessment of severity in proctocolitis. Issue 10 (October 1976) - Caprilli, R; Vernia, P; Colaneri, O; Torsoli, A
Abstract : Acid base balance was studied in 58 patients with active idiopathic proctocolitis; the condition of 10 of them was complicated by toxic megacolon. Arterial blood pH increased progressively with increased severity of the colitis and as the lesions became more widespread. Statistically significant differences were observed in pH values between the mild/moderate and severe forms and between the severe and complicated forms ('toxic megacolon'). A linear correlation was found between pH and the amount of intestinal gas, pulse rate, and plasma albumin.